INFLUENCE OF DIFFERENT DRIP IRRIGATION AND FERTIGATION LEVELS ON YIELD AND ECONOMICS OF HIGH DENSITY SUMMER SWEET CORN - LAKSHMI PRAYAGA, N. LAVANYA, P. LAXMINARAYANA, K.B. SUNEETHA DEVI, G. JAYASREE and (The Journal of Research, PJTSAU, 2022)
An experiment was conducted to study the effect of different drip irrigation and fertigation levels on yield and economics of high-density sweet corn at College Farm, College of Agriculture, PJTSAU, Hyderabad, during summer 2020 and 2021. The experiment consisted of twelve treatments laid out in Factorial Randomized Block Design (FRBD) replicated thrice. Three irrigation levels (Irrigation scheduled at 0.6 [I1], 0.8 [I2] and 1.0 Epan [I3] throughout the crop growth period) and four fertigation levels (application of 100% RDNK in differential dosage as per recommendation [F1], application of 100% RDNK in differential dosage as per crop coefficient curve [F2], application of 125% RDNK in differential dosage as per recommendation [F3] and application of 125% RDNK in differential dosage as per crop coefficient curve [F4] were included as treatments in this study. Among three irrigation levels, irrigation scheduled at 1.0 Epan recorded significantly higher gross returns, net returns and benefit cost ratio over 0.8 and0.6 Epan during both the years and in means. Lowest gross returns, net returns and B:C ratio were observed under 0.6 Epan. Among the four fertigation levels, application of 125 % RDNK in differential dosage as per crop coefficient curve recorded significantly higher gross returns, net returns and B:C ratio which were on par with application of 125 % RDNK in differential dosage as per recommendation.